2000
DOI: 10.1038/sj.ejcn.1600905
|View full text |Cite
|
Sign up to set email alerts
|

Digestibility of cocoa butter from chocolate in humans: a comparison with corn-oil

Abstract: Objective: To compare, in humans, the digestibility of moderate amounts of cocoa butter (30.7 gad) consumed in the form of chocolate as part of a normal western diet with that of a well-absorbed fat (corn oil); and hence determine whether, by virtue of its apparent low absorption, cocoa butter can be considered to be a low calorie fat. Design: Randomised, two-period crossover metabolic study, conducted under free-living conditions, but with strict control over food intake. Setting: Metabolic Unit, Nestle  Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 15 publications
1
22
0
1
Order By: Relevance
“…However, more recent human studies have reported that 18 : 0-rich fats are generally well absorbed (>90%), especially when fed with other dietary fats; for example, cocoa butter is relatively well absorbed, with digestibility values of 89-99% (Mitchell et al 1989;Denke & Grundy, 1991;Shahkhalili et al 2000). More variable results have, however, been obtained with randomised fats rich in 18: 0.…”
Section: Stearic Acid Triacylglycerol Structure and Digestionmentioning
confidence: 92%
“…However, more recent human studies have reported that 18 : 0-rich fats are generally well absorbed (>90%), especially when fed with other dietary fats; for example, cocoa butter is relatively well absorbed, with digestibility values of 89-99% (Mitchell et al 1989;Denke & Grundy, 1991;Shahkhalili et al 2000). More variable results have, however, been obtained with randomised fats rich in 18: 0.…”
Section: Stearic Acid Triacylglycerol Structure and Digestionmentioning
confidence: 92%
“…Others have also reported stearic acid to be well digested whether distributed in the sn-1 and sn-3 positions of the dietary TAG (49) or as a randomly interesterified stearic acid-rich fat (46,50 -52) . Human studies have also shown that the digestibility of palmitic acid is high in human subjects when in the outer positions (47,48) , or randomly distributed on all three positions of the glycerol (51) .…”
Section: Triacylglycerol Structure and Digestibilitymentioning
confidence: 99%
“…Shahkhalili et al (48) reported that following cocoa butter or maize oil (31 g/d) fed to male subjects for 2 weeks, there was no difference in the faecal fat excretion (mean 4·55 g/d) and digestibility relative to maize oil (99 %), although the proportion of stearic acid in the faeces during the cocoa butter period (1·9 g/d) was higher than during the maize oil period (41 v. 27 % respectively), but was compensated for by a decrease in the proportion of other faecal fatty acids (48) . Denke & Grundy (47) observed that following diets rich in beef tallow, native cocoa butter, butter fat and olive oil (23·6, 40·9, 12·4 and 3·7 g stearic acid/d respectively) using liquid formulated diets containing 40 % of energy from the test fat in ten male subjects for 3 weeks, the level of stearic acid excreted from beef tallow, native cocoa butter, butter fat and olive oil was within the usual range (1·4, 3·1, 1·2 and 1·2 g/d respectively), despite differences in the position of stearic acid in the dietary TAG.…”
Section: Triacylglycerol Structure and Digestibilitymentioning
confidence: 99%
“…Crude fat excretion of healthy men on various experimental diets (based mostly on natural triacylglycerols or their transesterified products) has generally varied between 4 and 12 g/day (Carey et al, 1983;Mitchell et al, 1989;Shahkhalili et al, 2000). The proportion of fatty acids (free, soaps or derived from acylglycerols) of the total lipids has rarely been reported, but the fatty acid concentration in feces has been between 0.2 and 6 g/day (Bonanome and Grundy, 1988;Denke et al, 1993), typically 2-4 g/day (see e.g.…”
Section: Fecal Lipid Content and Compositionmentioning
confidence: 99%